2015
DOI: 10.1021/acs.macromol.5b02202
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Proton Transport in Polymerized Ionic Liquid Block Copolymers: Roles of Block Length, Ionic Content, and Confinement

Abstract: Anhydrous proton transport has been investigated in a series of proton conducting polystyrene-blockpolymerized ionic liquid (PS-b-PIL) copolymers spanning a range of molecular weights and compositions. The PIL is a macromolecular analogue of imidazolium bis(trifluoromethane sulfonimide) (ImTFSI), a well-known proton conducting ionic liquid, and consists of imidazole linked to a polymer backbone via the 5-carbon. In contrast to prior work on nitrogen-linked imidazolium PILs, carbon-linked imidazolium has two ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 61 publications
(128 reference statements)
8
70
1
Order By: Relevance
“…The ion conductivity of poly(S‐ b ‐AEBIm‐TFSI) + Li‐TFSI/IL and the nonsulfonated PIL block copolymer, poly(S‐ b ‐AEBIm‐TFSI), from a previous study with a similar PIL composition to this study is also shown in Figure . Recent work by Segalman and co‐workers with a similar styrene‐based PIL block copolymer with mobile TFSI anions at a comparable PIL composition of 26 mol% PIL shows comparable anhydrous ion conductivity to poly(S‐ b ‐AEBIm‐TFSI) over the same temperature range. In comparison to the non‐sulfonated PIL block copolymer, the anhydrous ion conductivity for poly(SS‐Li‐ b ‐AEBIm‐TFSI) + Li‐TFSI/IL is over two orders of magnitude higher at moderate temperatures (60 °C).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The ion conductivity of poly(S‐ b ‐AEBIm‐TFSI) + Li‐TFSI/IL and the nonsulfonated PIL block copolymer, poly(S‐ b ‐AEBIm‐TFSI), from a previous study with a similar PIL composition to this study is also shown in Figure . Recent work by Segalman and co‐workers with a similar styrene‐based PIL block copolymer with mobile TFSI anions at a comparable PIL composition of 26 mol% PIL shows comparable anhydrous ion conductivity to poly(S‐ b ‐AEBIm‐TFSI) over the same temperature range. In comparison to the non‐sulfonated PIL block copolymer, the anhydrous ion conductivity for poly(SS‐Li‐ b ‐AEBIm‐TFSI) + Li‐TFSI/IL is over two orders of magnitude higher at moderate temperatures (60 °C).…”
Section: Resultssupporting
confidence: 59%
“…This class of block copolymer is unique, because of the distinct set of PIL properties that are incorporated within the block copolymer nanostructure, such as high ionic conductivity, high chemical, electrochemical, and thermal stability, and widely tunable chemical properties . PIL block copolymers are of interest for numerous potential electrochemical energy applications, most notably as anion exchange membranes for alkaline fuel cells and as solid polymer electrolytes in lithium‐ion batteries …”
Section: Introductionmentioning
confidence: 99%
“…In single ion conductors, metrics of fragility also relate to the decoupling of polymer and free ion motion mentioned above. Specifically, larger values of D correlate with more Arrhenius‐like behavior and more coupling between polymer and free ion motion . With the PILs under study herein, then, the most Arrhenius‐like, polymer dynamics‐dependent low‐temperature conductivity occurs with the smallest counteranion, i.e., I − , with low‐temperature behavior becoming less Arrhenius‐like and less coupled as anion size increases.…”
Section: Resultsmentioning
confidence: 74%
“…The first method involved adding ionic liquids directly into the casting solution or by impregnating them into polymer membrane matrix [201][202][203][204]. The second involved attaching or embedding the ionic liquids on a filler and then introducing them into the polymer matrix or grafting them directly onto the polymer [205][206][207].…”
Section: Proton-conducting Ionic Liquids (Pcils)mentioning
confidence: 99%